COOPERATION OF THE KYRGYZ REPUBLIC AND THE CIS COUNTRIES IN THE FIELD OF CERTIFICATION OF SCIENTIFIC PERSONNEL: ISSUES AND PROSPECTS OF DEVELOPMEN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Certification of highly qualified scientists in each state is carried out in its own way, based on the cultural, historical, socio-political features of the development of the state. In world practice, two systems of attestation of highly qualified scientists are most widely used: the Soviet model and the European one.
Keywords: scientific; scientific-pedagogical personnel; attestation of scientific workers